2007
DOI: 10.1002/zamm.200610325
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solution for three‐dimensional stresses in a short length FGM hollow cylinder

Abstract: This paper presents the general theoretical analysis of three-dimensional mechanical and thermal stresses for a short hollow cylinder made of functionally graded material. The steady-state temperature, displacements, and stresses distributions are derived due to the general mechanical and thermal boundary conditions, as functions of radial, circumferential and longitudinal directions. The material properties vary continuously along the thickness direction according to power functions of radial direction. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…They obtained these solutions by making use of the method of separation of variables and expressed it in terms of the summation of the Fourier series in the circumferential direction. Jabbari et al [22] making use of the generalized Bessel function and Fourier series solved the temperature and Navier equations analytically and offered a general theoretical analysis of three-dimensional mechanical and thermal stresses for a short hollow cylinder made of functionally graded material. In a study carried out by You et al [23], the deformations and stresses in thick-walled cylindrical vessels made of FGMs were obtained.…”
mentioning
confidence: 99%
“…They obtained these solutions by making use of the method of separation of variables and expressed it in terms of the summation of the Fourier series in the circumferential direction. Jabbari et al [22] making use of the generalized Bessel function and Fourier series solved the temperature and Navier equations analytically and offered a general theoretical analysis of three-dimensional mechanical and thermal stresses for a short hollow cylinder made of functionally graded material. In a study carried out by You et al [23], the deformations and stresses in thick-walled cylindrical vessels made of FGMs were obtained.…”
mentioning
confidence: 99%
“…Analytical studies have been performed in recent years [1–4]. Also numerical studies have been performed [5–26]. Function types to be used for grading of isotropic or anisotropic behavior for pressurized hollow structures are very diverse.…”
Section: Introductionmentioning
confidence: 99%
“…The thermoelastic solution was obtained by a stress function approach. Jabbari et al (2007) suggested a general theoretical analysis of three-dimensional mechanical and thermal stresses for a short hollow FGM cylinder by the generalized Bessel function and Fourier series. Goshima and Miyao (1991) analytically solved a long hollow circular cylinder subjected to transient internal heat generation due to x-ray radiation, while there is convection on its inner and outer surfaces.…”
Section: Introductionmentioning
confidence: 99%